Insights into the molecular basis of PRRXL1 function - Monteiro, César Bruno da Cunha (2013)
Correct perception of sensory stimuli by the brain involves different types of sensory neurons which require specific and functional networks. How do they differentiate into their specific subtypes, and how do they establish functional synapses, are questions that remain largely unsolved. Throughout the nervous system development, homeodomain transcription factors play a pivotal role in the control of proliferation, specificity, differentiation and establishing connectivity between neurons. Among the transcriptions factors involved in the differentiation of sensory neurons, Prrxl1 (paired related homeobox proteinlike 1) had received a special interest in our laboratory since it is involved specifically in the differentiation of nociceptive neurons within dorsal root ganglia (DRG) and their central targets within dorsal spinal cord. Prrxl1 is one of the few transcriptions factors that exhibit an expression in the primary afferent neurons and their central targets. This expression pattern suggests that Prrxl1 have an important role establishing connectivity between first order neurons and second order neurons. Indeed, analysis of Prrxl1-/- mice phenotype revealed that Prrxl1 is involved in several aspects of neuronal differentiation such as migration, axon guidance and the proper nociceptive behavior in adult individuals. Hence, Prrxl1 function might be based in the activation of a complex genetic program. Our recent findings had shown that Prrxl1 gene origin two transcripts, Prrxl1a and Prrxl1b, through the alternative splicing mechanism. Furthermore, Prrxl1a present several phosphorylation states which pattern throughout the development is variable. Hence, phosphorylation appear to have a regulatory role in Prrxl1 activity, however, kinases and phosphatases involved in this process, as well as other proteins that might interact with Prrxl1a/b remain unknown. The first objective of the present study was to characterize Prrxl1 interactome by the Yeast-Two-Hybrid system. However, it was not possible to achieve it due Prrxl1a and Prrxl1 specific C-terminal sequence, used as baits, to activate reporter genes transcription in the absence of any prey fused to an activation domain. Thus, the Yeast-Two-Hybrid approach used was not successful. On the other hand, aiming to characterize Prrxl1 genetic program in the developing spinal cord, was performed Chromatin Immunopercipitation followed by massive parallel sequencing (ChIP-Seq) using a Prrxl1 specific antibody and chromatin from the murine E14.5 dorsal half of the spinal cord. This approach allowed the identification of 939 candidate genes associated with the Prrxl1 binding sites obtained by ChIP-Seq. However, DNA-protein interaction did not mean that there is a transcriptional regulation. Hence, the second objective of the present study was to select a set of candidate genes from ChIP-Seq list, and to analyze their expression pattern in spinal cord and DRG, in wild type and Prrxl1-/- mice by in situ hybridization and Real Time PCR. Our study revealed that Dscaml1 and Sema3F are Prrxl1 direct targets in spinal cord and DRG, and Cdh4 and Efna5 are Prrxl1 direct targets only in DRG. These results suggest that Prrxl1 is involved in axon guidance and neuronal connectivity and, therefore, are in agreement with the Prrxl1-/- mice phenotype.